"Sustainability challenges cannot be understood from just one perspective or just one discipline": an interview with Dr. Maximilian Jungmann, Heidelberg University, about his interdisciplinary Marsilius Bridge Seminar "Sustainable Strategy Development” (Heidelberg inspirations for innovative teaching, 2024)
Ein Interview mit Dr. Maximilian Jungman von der Universität Heidelberg zu seinem interdisziplinären Marsilius Brückenseminar "Sustainable Strategy Development"
Gesehen am 07.01.2025